The effect of TiO2 addition on the thermal conductivity of Polymethylmetha acrylate, Polycarbonate and Polystyrene Polymers - Al-Maliki, Firas J. (Iraqi Journal of Physics, 2010)
Thermal conductivity measurement was done for specimens of Polystyrene/ titanium dioxide, Polycarbonate/ titanium dioxide and Polymethylmetha acrylate/ titanium dioxide composites for weight ratio of 1.9/ 0.1 and 1.8/ 0.2 wt% for different thickness of the samples. The experimental results show that the thermal conductivity is increased with the increasing of thickness of layers and with the weight ratio of TiO2